AMIR TEMUR'S ECONOMIC VIEWS ON STATE AND COMMUNITY MANAGEMENT - Mahsutaliev Abdusalom Hasanovich (Web of Journals Publishing, 2024)
This article explores the historical and national foundations of leadership, recommends principles for selecting a leader and economic ideas for public administration in Amir Temur’s work “Temur tuzuklari”
Keywords: Management, administrative rules, public administration, personnel issues, principles of selection of managers, executive decree.